2010
DOI: 10.2140/jomms.2010.5.161
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale analysis of nanoscale thin film considering surface effects: Thermomechanical properties

Abstract: The classical model for a thin film, based on continuum theory, is independent of size, and ignores surface effects. But the surface-to-bulk ratio becomes very large in small-scale structures such as nanofilms, nanowires, and nanobeams, and surface effects play an important role. Molecular dynamics simulation has been a conventional way to analyze these ultrathin structures, but structures in the range between submicro and micro are difficult to analyze by molecular dynamics simulation due to the restrictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The surface tension between water and the atmosphere is chosen as γ GL = 7.28 × 10 −2 N m −1 . The surface material parameters of the substrate are γ S = 1.0398 N m −1 , surface Lame parameters λ S = 15.6 N m −1 , μ S = −8.6 N m −1 , which are obtained from Choi et al [31]. The only unknown parameter for the interface layer is γ L , which can be obtained based on the target contact angle [11].…”
Section: (A) Validation Of the Surface Tension Effectmentioning
confidence: 99%
“…The surface tension between water and the atmosphere is chosen as γ GL = 7.28 × 10 −2 N m −1 . The surface material parameters of the substrate are γ S = 1.0398 N m −1 , surface Lame parameters λ S = 15.6 N m −1 , μ S = −8.6 N m −1 , which are obtained from Choi et al [31]. The only unknown parameter for the interface layer is γ L , which can be obtained based on the target contact angle [11].…”
Section: (A) Validation Of the Surface Tension Effectmentioning
confidence: 99%
“…19 The mechanical properties of the bulk material were also predicted by MD simulation for each configuration. Usually, they can be obtained from MD simulation or experiments.…”
Section: Surface Effects On the Dynamic Behavior Of Nanosized Thin Fimentioning
confidence: 99%
“…19 Therefore, the fundamental natural frequency of the NEMS resonator when surface effects were considered was about 30% lower than when surface effects were ignored for the ͑100͒/͓100͔ configuration at 3.1 nm ͑Fig. 19 Therefore, the fundamental natural frequency of the NEMS resonator when surface effects were considered was about 30% lower than when surface effects were ignored for the ͑100͒/͓100͔ configuration at 3.1 nm ͑Fig.…”
Section: Surface Effects On the Dynamic Behavior Of Nanosized Thin Fimentioning
confidence: 99%
“…Cho et al [2009] suggested a sequential multiscale method in order to determine initial surface stress and surface Lamé constants using a matching method based on a molecular dynamics (MD) simulation. As an extension of this multiscale model, a finite element analysis including thermomechanical properties was carried out by Choi et al [2010a].…”
Section: Introductionmentioning
confidence: 99%